Web Application Lifecycle: Combining Important Actors and Factors in Web Development - Ricky Jiandy (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2015)
In web application development, developers and business owners usually work together in developing of the web application based on business process from the enterprise. The web development integrate business process into web applications usually limit developers to invent growing web technology into enterprise web application. Basically web development lifecycle is based on SDLC, which integrate business process into application development process. This paper discusses the new approach to develop a web application using new web application lifecycle by combining factors (usability, accessibility, Quality of Service, etc.) and actors (users, owners, developers) in web development and separate business process development with a goal to enable developers invent latest web technology into web application.